Comparison between Power Dissipation and Propagation Delay on 6T SRAM Cell Design Using GDI Logic with Transmission Gate VMSA and Voltage Divider - Aditya, Reza; Harahap, Robby Kurniawan (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2024)
The rapid evolution of the semiconductor industry has witnessed shrinking portable and mobile devices alongside an increasing demand for extended battery life. Addressing the critical challenges of speed and battery life in digital devices, this paper investigated the effectiveness of innovative low-power design techniques. Focusing on the Gate Diffusion Input (GDI) approach, a recent advancement in the field, a comprehensive analysis revealed its significant potential for reducing power consumption in digital circuits. Additionally, a comparative analysis was conducted to evaluate the performance of conventional 6T GDI SRAM cells and their Modified 6T GDI SRAM with Voltage Divider, considering the influence of Sense Amplifiers. Simulation data demonstrated that Modified 6T SRAM designs, particularly the Voltage Divider and TGVMSA variants, achieved significantly lower power dissipation and delay despite having a larger cell area. Remarkably, the proposed design substantially improved power dissipation and propagation delay, achieving 1.3 ps, and 889.41mV at 1.8V shows that the suggested design enhances power dissipation and propagation delay. These findings suggest that the proposed design offers a promising strategy for enhancing power efficiency and performance in digital devices, thereby mitigating the limitations of battery life and speed in the modern technological landscape.